2014
DOI: 10.1558/cj.v33i2.26055
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of computer-based spaced repetition in foreign language vocabulary instruction: a double-blind study

Abstract: The purpose of the present paper is twofold; first, we present an empirical study evaluating the effectiveness of a novel CALL tool for foreign language vocabulary instruction based on spaced repetition of target vocabulary items. The study demonstrates that by spending an average of three minutes each day on automatically generated vocabulary activities, EFL students increased their long-term vocabulary retention rate three fold. Second, we demonstrate that the double-blind experiment design, which has become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(6 reference statements)
0
7
0
1
Order By: Relevance
“…Although most of the TMVD treatments did not involve teacher mediation, 60 studies (n = 73%) were conducted in class or in a computer lab; plus, in 5 cases, a part of the treatment was in class, i.e., only 16 studies investigated TMVD outside the formal educational settings. The latter were studies that incorporated mobile-assisted language learning (e.g., Amer, 2014;Andujar, 2016;Stockwell, 2010;Terantino, 2016), intercultural exchanges (e.g., Lin, 2016) and other CMC studies (e.g., Kozar, 2016;Yilmaz & Yuksel, 2011), and longitudinal studies (e.g., Chukharev-Hudilainen & Klepikova, 2016;Gobel & Kano, 2014) or studies of extramural language use (e.g., Jensen, 2017;Sylven & Sundqvist, 2012).…”
Section: Learning and Instructional Approachesmentioning
confidence: 99%
“…Although most of the TMVD treatments did not involve teacher mediation, 60 studies (n = 73%) were conducted in class or in a computer lab; plus, in 5 cases, a part of the treatment was in class, i.e., only 16 studies investigated TMVD outside the formal educational settings. The latter were studies that incorporated mobile-assisted language learning (e.g., Amer, 2014;Andujar, 2016;Stockwell, 2010;Terantino, 2016), intercultural exchanges (e.g., Lin, 2016) and other CMC studies (e.g., Kozar, 2016;Yilmaz & Yuksel, 2011), and longitudinal studies (e.g., Chukharev-Hudilainen & Klepikova, 2016;Gobel & Kano, 2014) or studies of extramural language use (e.g., Jensen, 2017;Sylven & Sundqvist, 2012).…”
Section: Learning and Instructional Approachesmentioning
confidence: 99%
“…Within the TELL tools, hyperlinks may also be used as memory aids by readily providing access to explanations, vocabulary and grammar. In addition, the use of memory aids may involve the recourse to flash cards, word walls, conjugation tables and computer adaptative software (Akyel & Erçetin, 2009;Chukharev-Hudilainen & Klepikova, 2016;Yang & Hsieh, 2015).…”
Section: Long-term Memorizationmentioning
confidence: 99%
“…Some earlier studies have identified the utilization of computer-mediated language learning as a good medium for long-term learning. Spaced repeating can assist users in building effective study patterns with an application while engaged in L2 learning [22][23][24][25][26][27]. Other studies showed more innovation, such as how to teach vocabulary to students by making lists of words more powerful and interesting through multimedia enhancement, and this was particularly applied to the English language [28][29][30].…”
Section: Introductionmentioning
confidence: 99%